Draft Five Year Plan 1978-83 Local Bodies Development - Planning Commission (Planning Commission, 1978)
Urbanisation in Madhya Pradesh has accelerated rapidly, with the 1971 census recording an urban population growth of 46.63% compared to 25.68% in rural areas, placing immense pressure on civic amenities such as housing, roads, drainage, sewage, markets, parks, and public latrines. The state’s 217 urban local bodies, including corporations, municipalities, and notified area committees, face severe financial constraints, limiting their ability to provide adequate services. During the Fifth Five Year Plan (1974–78), the annual plan allocations were grossly insufficient, totaling Rs. 147.73 lakhs over four years, whereas the average demand of local bodies was nearly Rs. 3 crores per year. Recognised development works under the plan included construction of roads, surface drainage, housing for municipal staff, firefighting equipment, and other urban infrastructure, with the government contributing 40% and local bodies 60% of costs. The Sixth Five Year Plan (1978–83) proposed a total outlay of Rs. 2.40 crores (Rs. 48 lakhs per year), far below the estimated Rs. 5 crores annually required to meet the growing needs of urban areas. Given the mounting liabilities and inadequate funding, it is evident that municipal services have deteriorated, necessitating a substantial upward revision of plan allocations to Rs. 4 crores for effective development of civil amenities, prevent further decline in service quality, and mitigate negative public perception.
Government of Madhya Pradesh Planning. Economics & Statistics Department
Government of Madhya Pradesh Planning. Economics & Statistics Department
Keywords: Urbanisation; Madhya Pradesh; Local Bodies; Civic Amenities; Financial Management; Municipal Development; Roads; Drainage; Public Facilities; Fifth Five Year Plan; Sixth Five Year Plan; Fiscal Outlay